„Wizja przeciw równaniu” Wokół popaździernikowego sporu o wyobraźnię twórczą - Stankowska, Agata (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The 4th volume of the series Polemika Krytycznoliteracka w Polsce („Critical Literary Argument in Poland”) is devoted to the dispute ongoing in Polish cultural life after the October thaw in 1956. The subject-matter was „liberated imagination” treated both as the source and as the effect of the creative process. The argument was opened by the famous essay Vision against equation. The new struggle of the Romantics with the Classics by Jerzy Kwiatkowski published in 1958 in „Życie Literackie”. The Adversaries were both critics (Włodzimierz Maciąg, Michał Głowiński, Zbigniew Bieńkowski, Ludwik Flaszen, Kazimierz Wyka), and poets(Jerzy Harasymowicz, Bohdan Drozdowski, Julian Przyboś, Tadeusz Różewicz, Zbigniew Herbert, Stanisław Czycz). The dispute ongoing in the esthetical reflections plane and, at least, in respect of social and political context of the epoch (war and Stalinism) had its equivalent in the discussions concerning the plastic arts, especially the Tachism.
„Vision against equation” About the post-October dispute over the creative imagination
Keywords: Jerzy Kwiatkowski; Włodzimierz Maciąg; Julian Przyboś; Bohdan Drozdowski; Michał Głowiński; Tadeusz Różewicz; Jan Brzękowski; polemika krytycznoliteracka